The Effect of the Thermosphere on Ionosphere Outflows - Krall, J.; Huba, J. D. (Frontiers in Astronomy and Space Sciences, 2021)
The Naval Research Laboratory (NRL) Sami2 is Another Model of the Ionosphere (SAMI2) and Sami3 is Also a Model of the Ionosphere (SAMI3) ionosphere/plasmasphere codes have shown that thermosphere composition and winds significantly affect H$^+$ outflows from the topside ionosphere. In particular, O density inhibits upward diffusion of O$^+$ from the ionosphere F layer, especially during solar maximum conditions. In addition, winds affect the quiet-time latitudinal extent of the F layer, affecting densities at mid-to-high latitudes that are the source of plasmasphere refilling outflows. Evidence for these effects is reviewed and prospects for forecasting these outflows are explored. Open questions for future research are highlighted.